2018
DOI: 10.1007/s11060-018-2892-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and survival of glioblastoma patients in Denmark: The Danish Neuro-Oncology Registry 2009–2014

Abstract: Glioblastoma patients had a poor overall survival but with several specific independent prognostic factors. Extensive cancer treatment was associated with an increasing survival in all age groups, but only half of the patients were sufficiently fit for a full regimen of postoperative combined radiochemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 27 publications
18
29
2
Order By: Relevance
“…These data must be considered with caution since those patients are not subject to randomization. Although more patients had resections !95% after the introduction of 5-ALA, the changes in postoperative performance status in our series was comparable to other studies [20,31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data must be considered with caution since those patients are not subject to randomization. Although more patients had resections !95% after the introduction of 5-ALA, the changes in postoperative performance status in our series was comparable to other studies [20,31].…”
Section: Discussionsupporting
confidence: 91%
“…Reports on population-based results over longer time periods are sparse but important since it more accurate reflects the group of patients that we meet on a daily basis [3,4,20,21]. The aim of the present study was to evaluate how the scientific progress in GBM treatment has been translated into clinical reality for the whole population of patients treated at a single Swedish university hospital from 1995 to 2015 and to what extent it may have influenced survival.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the crude incidence rate was 3.3/100,000 person-years and is in good accordance with the literature [ 1 ]. OS was 11.2 months, similar to the values obtained in population-based studies in the post-temozolomide era [ 28 30 ]. Survival rates were similar to US results [ 2 ], and intermediate between those of the RT-only arm and those of the RT–temozolomide arm in the EORTC–NCIC clinical trial [ 31 ].…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the survival times in the high-volume and medium-volume hospitals match those of other Nordic countries, while the survival time was slightly shorter in the low-volume hospital. For example, a Norwegian study (time period: 2004-2007, median age = 64 years) found a median survival time of 10.1 months [25] and a Danish study (time period: 2009-2014, median age = 66 years) found a median survival time of 11.2 months [26]. Moreover, studies from the U.S. (Surveillance, Epidemiology, and End Results Program [SEER]) have found median survival times of 15 and 9.7 months [27,28].…”
Section: Discussionmentioning
confidence: 99%